Análise fotogramétrica para predição de volune e comportamento respiratórios em adolescentes - Ripka, Wagner Luis (2012)
Introduction: There are several ways to evaluate the respiratory system, among them inductance plethysmography and three-dimensional kinematic analysis, methods of high cost and difficult transportability. The use of an alternative method based on the photographic image (photogrammetry) emerges as an instrument of low cost and easy transportation for respiratory analysis. Objective: The objective of this study was to correlate respiratory volumes obtained by spirometry standard equipment with a biomechanical model photogrammetric analysis of adolescents. Methods: 40 patients (19 boys and 21 girls) were evaluated, aged between 14 and 17 years. Individuals who showed some sort of respiratory obstruction or restriction were excluded. With the markers stickers, a mapping in five anatomical landmarks: projection of the umbilicus (Cod), inferior angle of 10th rib (ACd), projection of sternum manubriam (MEd), sternal xiphoid projection (AXd) and right spine iliac (EId). With each subject assessed in supine position, tests the Forced Vital Capacity (FVC) were requested, using a spirometer Care Fusion - Microloop. The test was repeated three times and filmed. Images of the films were extracted for the moment of maximum expiration and inspiration for photogrammetric processing of proof with better breathing. With the use a program commercially available, areas and lung volumes were defined for the region of upper and lower chest, as well as top and bottom abdomen. In addition to spirometric test body weight, height, body fat and thoracic length were measure. Results: the mean age was 15.40 ± 0.98 years. For body mass, height, fat percentage and thoracic length, average values of 61.29 ± 12.27 kg, 1.66 ± 0.09 m, 22.70 ± 6.49% and 25.54 ± 1.87 cm were found, respectively. When comparing boys and girls at the age difference was not found statistically significant. The photogrammetric analysis has found values strongly correlated with the spirometric measurements of FVC, forced expiratory volume in one second (FEV1), Peak Expiratory Flow (PEF) in addition to post test performed Inspiration (IP). There was a higher ventilatory mobility for boys than girls for Lower Chest and Lower and Upper Abdomen. It was possible to reach a regression R² = 0.866 for proof of FVC and R² = 0.776 for IP with the use of photogrammetry, presenting a standard error of 0.353 and 0.451, respectively. Conclusion: photogrammetry can be used to study thoracoabdominal movements by applying analytical two-dimensional and three-dimensional images acquired using a video camera being, applicable and reproducible. It was possible to verify respiratory behavior in adolescents including measurements on the image with the values measured using the spirometer. It was also possible to estimate the value of FVC and volume of air breathed in deep inspiration maneuver.